Neural mechanisms of emotion regulation and their role in endocrine and immune functioning: A review with implications for treatment of affective disorders. (December 2018) - Lopez, Richard B.; Denny, Bryan T.; Fagundes, Christopher P.
Highlights: Affective disorders impact psychological health and physical health, with increased inflammation a common co-occurring condition. Treatments for affective disorders are not always effective, as many were developed without reference to neurobiological mechanisms. Here, we review brain-based measures of emotion regulation strategies and their effects on mental and physical health. Regions of prefrontal cortex play a key regulatory role in autonomic, endocrine, and attendant immunological processes. We conclude by proposing a neuro-immuno-affective framework that targets regions of prefrontal cortex with emotion regulation skills training. Abstract: In the past century, medical progress has helped increase life expectancy and improve health outcomes more generally. Despite this progress, psychiatric disorders—especially affective disorders including depressive and anxiety disorders—are quite common and have been linked to dysfunction in endocrine and immune systems. In this review, we discuss neurobiological correlates of emotion regulation strategies and their effects on mental and physical health. Some of these correlates, namely sub-regions of prefrontal cortex, also play a key regulatory role in autonomic, endocrine, and immunological processes. Given this functional overlap, we propose a novel neuro-immuno-affective framework that targets improving emotion regulation, in order to: (1) reduce negative affect associated with depressive and/or anxiety disorders; and (2) alter endocrine and immune system functioning (e.g., reduce inflammation)—via changes in activity within (and connectivity between) brain systems that support (successful) emotion regulation. We conclude by arguing that such a framework can be adapted for psychiatric treatment protocols that holistically incorporate neural and immunological biomarkers to promote mental and physical health.